Determining Significant Factors Influencing Malaysian Construction Business Performance in International Markets - Isa, Che Maznah Mat; Saman, Hamidah Mohd; Preece, Christopher Nigel (Penerbit Universiti Sains Malaysia, 2015)
Market expansion into foreign markets has become increasingly important for construction businesses, including Malaysian contractors. It is therefore imperative that these firms are able to sustain performance in international markets. This paper aims to determine the significant factors influencing the Malaysian contractors' performance in international markets. This study adopts a mixed method using questionnaires that were sent to 115 construction firms as a sampling frame. The quantitative findings were further validated through in-depth interviews with five firms currently operating at the international level. It was found that the firms' profit targets based on return on investment and revenues supported by the firms' competitive advantages due to employees' capabilities and competencies have significantly influenced the firms' performance. However, further insights disclosed that having strong and stable human relationships were very important to enhancing the firms' performance in international markets. The findings build further understanding of international strategies for construction in developing countries. Finally, the study identifies the need to develop a suitable tool to measure firms' performance by taking into consideration the complex elements within the identified significant influencing factors.